Pharmacovigilance Perception and Knowledge Among Pharmacists and Interns in Saudi Arabia - Alshayban D; Mahmoud MA; Islam MA; Alshammari S; Alsulaiman D (Dove Medical Press, 2020)
Dhfer Alshayban,1 Mansour Adam Mahmoud,2 Md Ashraful Islam,1 Shouq Alshammari,1 Duaa Alsulaiman3 1Department of Pharmacy Practice, College of Clinical Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam 31441, Saudi Arabia; 2Department of Clinical and Hospital Pharmacy, College of Pharmacy, Taibah University, Al-Madinah Al-Munawarah, Saudi Arabia; 3Pharmacy Division, King Fahad University Hospital, Alkhobar, Saudi ArabiaCorrespondence: Mansour Adam MahmoudDepartment of Clinical and Hospital Pharmacy, College of Pharmacy, Taibah University, Al-Madinah Al-Munawarah, Saudi ArabiaEmail mammm.99@gmail.comAim: The aim of this study was to determine and compare the level of knowledge and perception of ADRs reporting and pharmacovigilance among interns and hospital pharmacists in different health-care settings in Saudi Arabia.Methods: A cross-sectional study was conducted among pharmacists and pharmacy interns in different hospitals in Saudi Arabia. A total of 315 participants completed the self-administered and validated questionnaire during the period from August 2018 to March 2019.Results: There was poor perception and knowledge of pharmacovigilance and ADRs reporting among pharmacists as well as intern pharmacists. However, pharmacists had better knowledge score compared to interns (P=0.043). Most of the respondents believed that ADRs reporting is important. The majority of both interns and pharmacists stated that they did not receive adequate education about pharmacovigilance during their undergraduate or internship program.Conclusion: There is a gap in knowledge and perception about pharmacovigilance among practicing pharmacists and new pharmacy graduates. Drug safety fundamentals and policies should be taught to undergraduate pharmacy students in Saudi Arabia.Keywords: pharmacovigilance, adverse drugs effects, safety, pharmacists, Saudi Arabia